Analisis Optimalisasi Teknologi Digital di Era Revolusi Industri 4.0 dalam Mengembangkan Kawasan Industri Pariwisata Halal guna Meningkatkan Perekonomian Lokal Kecamatan Gunungpati Kota Semarang - Moch Faizal Rachmadi (Jurnal DinamikA, 2020)
The use of appropriate digital technology can be an opportunity for Indonesia to develop its tourism sector to become a halal tourism industry to improve the national economy. Gunungpati District is one of the regions that has superior potential in the field of tourism. However, the absence of a halal tourism industry area and the use of technology that is not maximized make the tourism sector not too attractive to the wider community. Therefore, efforts are needed to optimize the flow of this digital technology massively. The purpose of this study is to improve the use of digital technology in realizing Gunungpati District into a halal tourism area. The method used in this study is descriptive qualitative analysis method with secondary data to describe the phenomena that occur in the field in explaining the data to support this work. Based on the study conducted it can be concluded that the use of appropriate technology can improve local and national economies through halal tourism industry.Keywords: the halal tourism industry, local economy, industrial revolution 4.0, digital technology.